Rhizospheric Fungus: Morphological Characterization Of Rhizosphere Flower On Onion Plant In Enrekang District - Hikmahwati hikmahwati Hikmahwati; Fitrianti Fitrianti; Suharman Suharman (LPPM UNIVERSITAS ISLAM KUANTAN SINGINGI, 2022)
The control of moler disease caused by Fusarium oxysporum on shallot plants in Enrekang Regency still relies on the use of chemical fungicides. Plants that are symbiotic with microbes will produce phytohormones optimally so that it will trigger the tolerance level of plants to abiotic and biotic stresses including plant pathogens, so it is necessary to explore the rhizosphere fungi of onion plants in Enrekang Regency to identify morphologically. This study used a red onion soil rhizosphere soil sample taken at the shallot farming center in Enrekang Regency, isolation and testing were carried out in the plant disease laboratory of Hasanuddin University. The results achieved were 20 isolates with 5 genera of fungi namely Fusarium on isolates 1,2,4,12 and 13, Gliocladium on isolates number 15,